2023
DOI: 10.1002/smll.202207663
|View full text |Cite
|
Sign up to set email alerts
|

Centimeter‐Sized Piezoelectric Single Crystal of Chiral Bismuth‐Based Hybrid Halide with Superior Electrostrictive Coefficient

Abstract: The lead‐free hybrid perovskite piezoelectrics possess advantages of easy processing, light weight, and low‐toxicity over inorganic ceramics. However, the lack of understanding in structure–property relationships hinders exploration of new molecular piezoelectric crystals with excellent performances. Herein, by introducing chiral α‐phenylethylammonium (α‐PEA+) cations into bismuth‐based hybrid halides, centimeter‐sized (R‐α‐PEA)4Bi2I10 and (S‐α‐PEA)4Bi2I10 single crystals with a superior piezoelectric voltage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 72 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Organic-inorganic hybrid metal halides combine the properties of inorganic and organic components and have the characteristics of flexible crystal structure, highly adjustable band gap, and luminescence effect. [1][2][3] They can be widely used in ferroelectric materials, 4 piezoelectric material, 5 and other materials. [6][7][8] The introduction of chiral organic molecules into organic-inorganic hybrid metal halides can obtain organic-inorganic metal halides with chiral properties.…”
Section: Introductionmentioning
confidence: 99%
“…Organic-inorganic hybrid metal halides combine the properties of inorganic and organic components and have the characteristics of flexible crystal structure, highly adjustable band gap, and luminescence effect. [1][2][3] They can be widely used in ferroelectric materials, 4 piezoelectric material, 5 and other materials. [6][7][8] The introduction of chiral organic molecules into organic-inorganic hybrid metal halides can obtain organic-inorganic metal halides with chiral properties.…”
Section: Introductionmentioning
confidence: 99%
“…Zero-dimensional (0D) organic-inorganic hybrid metal halides (OHMHs) have emerged as promising candidates in the field of advanced anti-counterfeiting luminescent materials due to their unique and diverse "host-guest" structures, highly efficient stimulated emission, and tunable photoluminescent properties. [9][10][11][12][13] Currently, there are numerous anti-counterfeiting applications based on zero-dimensional materials, such as Cu-based, [14] Sbbased, [11] Zr-based, [15] and In-based. [5] But most of these materials are usually limited to two emission colors, so information can only be decrypted through one key.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some studies evaluating the stability of various lead-free metal halides based on Bi­(III) and Sb­(III) for up to a year, there are only scarce reports about the environmental stability of chiral lead-free MHS. In particular, Wu et al developed a 1D semiconductor, namely, (C 9 H 14 N)­SbCl 4 (C 9 H 14 N = N , N ,4-trimethylaniline) with high second harmonic generation (SHG) response, which is air-stable for 3 months, Moon et al reported the synthesis of 0D [(( R / S )-C 8 H 12 N) 4 ]­[Bi 2 Br 10 ], (C 8 H 12 N = 1-phenyl-ethylammonium) which is stable in humid air for 1 month, Tao et al, acquired the 0D ( R -α-PEA) 4 Bi 2 I 10 and ( S -α-PEA) 4 Bi 2 I 10 compounds which are air-stable for 4 months, while Maiti and Pal synthesized the 0D ( R / S -MBA) 4 Bi 2 Br 10 materials which are air-stable for 15 days …”
Section: Introductionmentioning
confidence: 99%